Construction and Characterization of Adenovirus Vectors Encoding Aspartate-β-Hydroxylase to Preliminary Application in Immunotherapy of Hepatocellular Carcinoma. (15th July 2018) - Zhou, Yujiao; Liu, Feifei; Li, Chengmin; Shi, Guo; Xu, Xiaolei; Luo, Xue; Zhang, Yuanling; Fu, Jingjie; Zeng, Aizhong; Chen, Limin
Abstract : Dendritic cells (DCs) harboring tumor-associated antigen are supposed to be a potential immunotherapy for hepatocellular carcinoma (HCC). Aspartate- β -hydroxylase (AAH), an overexpressed tumor-associated cell surface protein, is considered as a promising biomarker and therapeutic target for HCC. In this study, we constructed adenovirus vector encoding AAH gene by gateway recombinant cloning technology and preliminarily explored the antitumor effects of DC vaccines harboring AAH. Firstly, the total AAH mRNA was extracted from human HCC tissues; the cDNA was amplified by RT-PCR, verified, and sequenced after TA cloning. Gateway technology was used and the obtained 18T-AAH was used as a substrate, to yield the final expression vector Ad-AAH-IRES2-EGFP. Secondly, bone marrow-derived DCs were infected by Ad-AAH-IRES2-EGFP to yield AAH-DC vaccines. Matured DCs were demonstrated by increased expression of CD11c, CD80, and MHC-II costimulatory molecules. A dramatically cell-killing effect of T lymphocytes coculturing with AAH-DCs on HepG2 HCC cell line was demonstrated by CCK-8 and FCM assays in vitro. More importantly, in an animal experiment, the lysis effect of cytotoxic T lymphocytes (CTLs) on HepG2 cells in the AAH-DC group was stronger than that in the control groups. In conclusion, the gateway recombinant cloning technology is a powerful method of constructing adenovirus vector, and the product Ad-AAH-IRES2-EGFP may present as a potential candidate for DC-based immunotherapy of HCC.